Lean manufacturing in a hospital product manufacturer: implementation and evaluation in the perception of managers - Nunes, Rogério da Silva; Jacobsen, Alessandra de Linhares; Cardoso, Rodrigo dos Santos (Revista de Administração da UFSM, 2019)
The use of lean production in organizations, which aims to broaden your results using fewer resources, that is, to increase productivity producing essentially necessary and eliminating what does not add value to clients, requires actions that include mapping of success environments and organization’s readiness for change management. Hence we have the current case study, descriptive, which presents the implementation of lean manufacturing in the textile plant in Blumenau (Santa Catarina) that manufactures medical products from a company with three manufacturing units. Next, there were interviews with thirteen managers and staff who participated in the lean manufacturing implementation process in the unit in focus. As a result, we identified that the requirements and preparations for the deployment mentioned are directed to a behavioral change that includes preparation of leadership, aligned with the organization’s strategy, which needs to be deployed to all areas. Also featured are the stages of implementation and attempts to institutionalize the environment provided by the principles of lean manufacturing. It concludes with the identification of categories of analysis for the changes arising from the aforementioned deployment.